new lens to media competence of gender divide in digitalized era - Yee Ling Ching; Ker Yuek Li; Nurul Farhana Jumaat (Journal of ICT in Education, 2022)
Living in the information explosion era, media competence has been indicated as a possible strategy for addressing the problems of misinformation and fake news. Thus, being media literate has become important in this modern world. However, the gender digital divide which is the unequal access to media use among men and women has been identified as one of the forms of the digital divide. Besides, there is a disparity in knowledge delivery happen in between tertiary education and school level. University students and people in industries receive a better comprehensive knowledge of media competence; while at the school level, the focus was more on information and language literacy. Considering higher education plays an important role in shaping an individual’s mindset, this study identifies the media competence of Malaysian university students and gender differences among them based on the competence of accessing, analyzing, evaluating, and communicating. In order to measure the differences between male and female undergraduates on the media competencies, descriptive analysis, and t-tests were conducted separately for each of the research questions. There are 362 university students participated in this study. An online survey is an instrument for data collection. The results show that there are no significant differences in the ability to evaluate and analyze between male and female undergraduates. In contrast, gender disparity is shown in the ability to access and communicate competencies, where females achieved better scores compared to males. This finding has reflected the insufficient media competence practice in the education system although university students are considered heavy media users in society. The result of this study is expected to contribute to relevant organizations or institutions to take effective measures to reduce the gender gap in media competence.